The practice of regular physical exercise in the context of self-image identification in larger persons is relevant, but is not associated with a high self-image (Research, Society and Development, 2025)
Body image is characterized by cognitive understanding, which combines with various reflections on body aesthetics. With this characterization, the objective of this study is to identify the self-image of elderly subjects who practice physical exercise. The study with a sample of 84 elderly people, 68 women and 16 men aged between 60 and 79 years (CI: 95%, p